2014
DOI: 10.1016/j.celrep.2014.09.056
|View full text |Cite
|
Sign up to set email alerts
|

A Direct Regulatory Interaction between Chaperonin TRiC and Stress-Responsive Transcription Factor HSF1

Abstract: Summary Heat Shock Transcription Factor 1 (HSF1) is an evolutionarily conserved transcription factor that protects cells from protein misfolding-induced stress and apoptosis. The mechanisms by which cytosolic protein misfolding leads to HSF1 activation have not been elucidated. Here we demonstrate that HSF1 is directly regulated by TRiC/CCT, a central ATP-dependent chaperonin complex that folds cytosolic proteins. A small molecule activator of HSF1, HSF1A, protects cells from stress-induced apoptosis, binds TR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
123
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(126 citation statements)
references
References 60 publications
3
123
0
Order By: Relevance
“…Although other molecular chaperones, such as heat shock proteins, could be easily induced by activating HSF1, expression of the eukaryotic chaperonin TRiC hetero-oligomeric complex is not regulated by HSF1 transcriptional activity. However, a recent study has revealed that HSF1 is regulated by TRiC (35). Because TRiC directly interacts with HSF1 and represses its transcriptional activity, disturbance of the interaction results HSF1 target gene expression, such as hsp70.…”
Section: Discussionmentioning
confidence: 99%
“…Although other molecular chaperones, such as heat shock proteins, could be easily induced by activating HSF1, expression of the eukaryotic chaperonin TRiC hetero-oligomeric complex is not regulated by HSF1 transcriptional activity. However, a recent study has revealed that HSF1 is regulated by TRiC (35). Because TRiC directly interacts with HSF1 and represses its transcriptional activity, disturbance of the interaction results HSF1 target gene expression, such as hsp70.…”
Section: Discussionmentioning
confidence: 99%
“…HSF1A suppresses toxicity in cell and tissue culture models of HD and SCA-3/MJD and appears to activate HSF1 by impairing the activity of TRiC, a recently discovered negative regulator of HSF1. HSF1A treatment blocks the direct interaction between TRiC and HSF1, thereby eliciting an HSR (137, 138). Although the precise mechanism by which F1 activates HSF1 is unknown, F1 treatment increases the expression of chaperones and antioxidant enzymes and markedly suppresses polyQ toxicity in C. elegans and tissue culture models of HD.…”
Section: Pharmacological Enhancement Of the Proteostasis Network As Amentioning
confidence: 99%
“…The activation and attenuation cycle of HSF1 in the HSR includes at least four steps: (1) De-repression & trimerization: upon cell stress, the influx of misfolded proteins prevents HSP70, HSP90, TRiC and perhaps other chaperones from binding to HSF1 monomers. This alleviates the repression of HSF1 by chaperones and is followed by conversion of the monomer to DNA binding competent trimers [911], (2) Translocation to the nucleus: HSF1 can exist either constitutively in the nucleus or in the cytoplasm. Upon protein misfolding, HSF1 translocates to the nucleus and drives transcription [2].…”
Section: Hsf1 Directs the Dynamic Hsr For Stress Adaptation And Protementioning
confidence: 99%